Experimental and Computational Study of Injectable Iron(III)/Ultrashort Peptide Hydrogels: A Candidate for Ferroptosis‐Induced Treatment of Bacterial Infections - Capucine Loth; Florent Barbault; Cécile Guégan; Flora Lemaire; Christophe Contal; Alain Carvalho; Sophie Hellé; Marie Champion; Halima Kerdjoudj; Delphine Chan‐Seng; Lydie Ploux; Fouzia Boulmedais (Small Science)
Injectable hydrogels are promising candidates as local drug delivery platforms for the treatment of infected wounds. Self‐assembled small peptide hydrogels are of interest due to their high biocompatibility, degradability, and ease of synthesis. This study describes the formation of an injectable hydrogel based on the self‐assembly of Fmoc‐FFpY (Fmoc: fluorenylmethoxycarbonyl, F: phenylalanine, pY: tyrosine phosphate) triggered by electrostatic interactions in the presence of Fe3+ ions. Stabilized by H bonding and π–π stacking, the hydrogels exhibit high mechanical stiffness with a G′ (storage modulus) of ≈8000 Pa and a self‐recovery up to G′ ≈100 Pa. Peptide self‐assembly yields β‐sheets twisted into fibrillar helices of 12 nm in diameter and pitch. Molecular dynamics simulations confirm 1) the aggregation of Fmoc‐FFpY in the presence of Fe3+ and the adopted secondary structure and show that 2) the aggregated Fmoc‐FFpY/Fe3+ disrupts the bacterial membrane of Staphylococcus aureus and Pseudomonas aeruginosa, favoring the passive entry of Fe3+ into the pathogen. In full agreement with the simulations, the hydrogels exhibit antibacterial activity against both bacteria, likely due to the increased Fe3+ entry into the cell, resulting in enhanced production of reactive oxygen species. This work paves the way for ferroptosis‐inducing treatment of bacterial infections using injectable ultrashort peptides.